Effect of time dependent morphological parameters of nanoclusters on perikinetic heat conduction and induced micro-convection mechanisms of oxide based nanofluids. Issue 3 (4th May 2018) - Kundan, Lal; Mallick, Soumya Suddha
ABSTRACT: The article represents an experimentally supported quantitative analysis to observe the effect of time, temperature, nanoclusters' morphology, and instantaneous volume fractions on perikinetic heat conduction and Brownian motion-based induced convection mechanisms of oxide (Al2 O3 and TiO2, size 25–30 nm) based nanofluids. The appropriate models of thermal conductivity have been introduced to study the effect of various parameters such as; varying volume fractions, suspensions' stabilities, nanoclusters' growth, temperature, and the liquid layering. The developed model could predict the thermal conductivity enhancements of nanofluids within the accuracy of ± 0.5% to ± 4.5.0% in the temperature range from 20°C to 50°C. Abbreviations : DI: De-ionized water; DLS: Dynamic light scattering; XRD: X-rays diffraction; TEM: Transmission electronic microscope; SDBS:Sodium dodecyl benzene sulphonate. Figure Effect of temperature on the Brownian Reynold number for Al2 O3 -H2 O and TiO2 -H2 O nanofluids. Abstract :